Maternal, neonatal, and child health systems under rapid urbanization: a qualitative study in a suburban district in Vietnam - Jongho Heo; Seung Yun Kim; Jinseon Yi; Soo-Young Yu; Da Eun Jung; Sangmi Lee; Ju Youn Jung; Hyunsuk Kim; Ngan Do; Hwa-Young Lee; You-Seon Nam; Van Minh Hoang; et al. (BMC, 2020)
Abstract Background Vietnam has been successful in increasing access to maternal, neonatal, and child health (MNCH) services during last decades; however, little is known about whether the primary MNCH service utilization has been properly utilized under the recent rapid urbanization. We aimed to examine current MNCH service utilization patterns at a district level. Methods The study was conducted qualitatively in a rural district named Quốc Oai. Women who gave a birth within a year and medical staff at various levels participated through 43 individual in-depth interviews and 3 focus group interviews. Results Primary MNCH services were underutilized due to a failure to meet increased quality needs. Most of the mothers preferred private clinics for antenatal care and the district hospital for delivery due to the better service quality of these facilities compared to that of the commune health stations (CHSs). Mothers had few sociocultural barriers to acquiring service information or utilizing services based on their improved standard of living. A financial burden for some services, including caesarian section, still existed for uninsured mothers, while their insured counterparts had relatively few difficulties. Conclusions For the improved macro-efficiency of MNCH systems, the government needs to rearrange human resources and/or merge some CHSs to achieve economies of scale and align with service volume distribution across the different levels.